A method for preparing basalt-like material by synergistically using red mud and gold tailings

Through the method of collaborating the preparation of new imitation basalt materials with red mud and goldtails, the existing imitation basalt materials have been solved, and granular imitation basalt materials with high strength and low hazards have been produced, achieving efficient utilization of resources and environmental protection.

CN119176683BActive Publication Date: 2025-03-07SHANDONG HENGYUAN WASTE UTILIZATION TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411676134.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Existing imitation basalt materials are costly and have safety risks when used in the construction field, especially fiber materials that may cause lung diseases.

Method used

The method of collaborating red mud and goldtails to prepare new imitation basalt materials is used to produce granular imitation basalt materials through steps such as raw material treatment, mixing, granulation and wetting agent spraying. This method simplifies the process flow, reduces production costs, and enhances the performance of the material with a wetting agent.

Benefits of technology

The improvement of concrete and asphalt strength by imitation basalt materials has been achieved, which reduces the harm to the human lungs, solves the environmental pollution and resource waste of red mud and goldtails, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a method for preparing a new basalt-like material by using red mud and gold tailings in coordination, and relates to the technical field of building materials. The gold tailings with a moisture content of 15-25% below 200 mesh are selected; the red mud with a moisture content of less than 5% is selected; the gold tailings and red mud in step one are sent to a vertical turbulent mixer for mixing and stirring, and an admixture is added to obtain a mixed material; the mixed material is sent to a roasting kiln for calcination, and after the calcination is completed, it is sent to a cooler to be cooled to below 50°C, and then the cooled mixed material is crushed by a crusher and sent to a stirring kettle, and a first impregnating agent is added to the stirring kettle at the same time, and after the stirring is completed, the material in the stirring kettle is sent to a high-pressure roller granulator for extrusion granulation; the primary particles are sent to a spraying device to spray a second impregnating agent, and then sent to a drying device for drying again. By this, the granular imitation basalt material will not produce needle-like objects similar to asbestos, which reduces the harm caused by the imitation basalt material to the human lungs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for preparing a new basalt-like material by using red mud and gold tailings in a coordinated manner. Background Art

[0002] Red mud is the polluting waste residue discharged when the aluminum industry extracts alumina. Generally, for every ton of alumina produced, 1.0 to 2.0 tons of red mud are produced. A large amount of red mud cannot be fully and effectively utilized and can only be piled up in large areas of yards, occupying a large amount of land and causing serious pollution to the environment. About 70 million tons of red mud are produced worldwide each year. The production of a large amount of red mud has caused many direct and indirect impacts on human production and life. Therefore, it is urgent to minimize the production and harm of red mud and realize multi-channel and large-scale resource utilization.

[0003] Similarly, gold tailings, as a byproduct, also face the problem of how to utilize them. At present, gold tailings have gradually been used in the field of building materials, but a large number of fine-grained tailings (less than 200 mesh) are difficult to obtain large-scale, high-value-added utilization. Therefore, it is necessary to explore ways to comprehensively utilize them on a large scale to improve the comprehensive utilization rate of tailings and realize the transformation of tailings from waste to treasure.

[0004] Basalt is the best material for repairing roads, railways, and airport runways. Basalt has the advantages of wear resistance, low water intake, poor electrical conductivity, strong compression resistance, low crushing value, strong corrosion resistance, and asphalt adhesion. It is internationally recognized as the best cornerstone for the development of railway and road transportation. The main components of basalt are silicon dioxide, aluminum oxide, iron oxide, calcium oxide, (and a small amount of potassium oxide), among which silicon dioxide has the highest content, accounting for about 45% to 50%.

[0005] The main components of red mud and gold tailings are SiO2, Al2O3, CaO, Fe2O3, etc. Therefore, we can use red mud and gold tailings to produce imitations of basalt - imitation basalt, and then apply the imitation basalt to the construction field to realize waste utilization.

[0006] Most of the existing basalt-like technologies are for imitating basalt fibers, such as the Chinese patent with application number "201410498584.X", which discloses "a method for preparing continuous basalt fibers using industrial solid waste as raw materials", and its technical solution is "the present invention uses industrial solid waste with similar chemical composition to basalt as the main raw material, and iron tailings, titanium-containing slag, alumina red mud and the like as additives to prepare continuous basalt fibers, reasonably proportions the amount of each component, gives full play to the synergistic effect of each component, and makes full use of the main components of solid waste, silicon dioxide and alumina, iron oxide contained in iron tailings, titanium oxide contained in titanium-containing slag and alumina contained in alumina red mud. The continuous basalt fibers prepared by coupling various components have better performance than traditional continuous basalt fibers, and effectively realize the efficient utilization of solid waste."

[0007] Another example is the Chinese patent with application number "CN201811589234.9", which discloses "a kind of imitation basalt fiber" and its technical solution is "its components include 10-50 parts of fly ash, 5-15 parts of coal gangue, 5-10 parts of iron tailings, 1-10 parts of titanium-containing slag, and 10-70 parts of red mud. All the above raw materials are processed into chopped fibers by high-temperature melt drawing at 1400-1500℃ to obtain imitation basalt fiber. All the components of this invention are industrial solid waste, which makes full use of solid waste and provides a very good utilization way for industrial solid waste."

[0008] The above processes all involve similar textile techniques, such as drawing and winding. However, the process is too complicated, resulting in high production costs and is not suitable for large-scale use in the construction field. Moreover, basalt fiber is similar to asbestos. When it is used in road paving, as the road continues to wear and tear, the basalt fiber is exposed to the outside. Due to its light volume, it will flow with the air, which will cause pedestrians to inhale it and cause lung diseases.

[0009] Therefore, how to produce low-cost, higher safety factor imitation basalt materials suitable for the construction field is a current problem. Summary of the invention

[0010] In view of the above defects, the purpose of the present invention is to provide a method for preparing a new basalt-like material by synergistically using red mud and gold tailings, aiming to solve the problem in the prior art that the basalt-like material has high cost and involves safety hazards when used in the construction field.

[0011] In order to solve the above technical problems, the technical solution of the present invention is:

[0012] A method for preparing a new basalt-like material by using red mud and gold tailings in a coordinated manner comprises the following steps:

[0013] Step 1, raw material processing;

[0014] The gold tailings slurry discharged from the concentrator is sorted by a cyclone, and the slurry below 200 mesh is concentrated and filtered by a concentrator to obtain gold tailings with a moisture content of 15-25%; red mud with a moisture content of less than 5% is selected and crushed by a double-roll crusher;

[0015] Step 2, mixing materials;

[0016] The gold tailings and red mud in step 1 are sent to a vertical turbulent mixer for mixing and stirring, and an admixture is added during the stirring period to obtain a mixed material after the stirring is completed;

[0017] Step three, material granulation;

[0018] The mixed material in step 2 is sent to a roasting kiln for calcination, and after calcination, it is sent to a cooler to cool to below 50°C, and then the cooled mixed material is crushed by a crusher and sent to a stirring kettle, and a first impregnating agent is added to the stirring kettle. After stirring, the material in the stirring kettle is sent to a high-pressure double-roll granulator for extrusion granulation to obtain a raw material, and the raw material is screened by a vibrating screen and sent to a drying device for drying, and primary particles are obtained after drying;

[0019] Step 4: spraying the wetting agent;

[0020] The primary particles are sent to the spraying equipment to spray the second impregnating agent. After the spraying is completed, they are left to stand for 2-3 hours, and then sent to the drying equipment for drying again to obtain the imitation basalt particles. The imitation basalt particles are waited to cool naturally to 40°C, and then packaged and stored.

[0021] Wherein, in step 2, by weight, the red mud is 40-55 parts, the gold tailings is 20-40 parts, and the admixture is 5-20 parts.

[0022] The admixture is composed of gypsum, fly ash and coal gangue powder; by weight, the gypsum is 10-30 parts, the fly ash is 10-30 parts, and the coal gangue powder is 10-40 parts.

[0023] Among them, in step three, the mixed material is continuously fed into the tail of the roasting kiln, the temperature range of the tail of the kiln is 650-750°C, the temperature range of the head of the kiln is 1100-1500°C, and the firing time is 30-50min.

[0024] Wherein, in step three, by weight, the first impregnating agent is 25-35 parts, and the mixed material is 65-75 parts.

[0025] The first impregnating agent is composed of a first film-forming agent, a first coupling agent, polysorbate 20, silicone oil and deionized water. By weight, the first film-forming agent is 10-18 parts, the first coupling agent is 7-11 parts, polysorbate 20 is 2-6 parts, silicone oil is 3-4 parts, and the rest is supplemented by deionized water.

[0026] Wherein, the first film-forming agent is obtained by modifying amylose with a modifier, wherein the amylose includes but is not limited to corn starch, sweet potato starch, and potato starch, and the modifier is composed of a mixture of aluminum phosphate, diaminophosphoric acid, diethanolamine, and deionized water. In terms of weight, the modifier consists of 13-15 parts of aluminum phosphate, 16-25 parts of diaminophosphoric acid, 22-30 parts of diethanolamine, and 30-49 parts of deionized water.

[0027] The first coupling agent is composed of 40-45 parts of γ-aminopropyltriethoxysilane, 25-35 parts of γ-methacryloxypropyltrimethoxysilane, and 20-25 parts of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.

[0028] The second wetting agent is composed of a second film-forming agent, a second coupling agent, lauryl alcohol, hexadecyltrimethylammonium chloride and deionized water. By weight, the second film-forming agent is 12-15 parts, the second coupling agent is 5-7 parts, the lauryl alcohol is 3-5 parts, the hexadecyltrimethylammonium chloride is 1-3 parts, and the rest is supplemented by deionized water.

[0029] Wherein, the second film-forming agent is water-based polyurethane; and the second coupling agent is a borate coupling agent.

[0030] After adopting the above technical solution, the beneficial effects of this solution are:

[0031] First, by using the first impregnant and the second impregnant together, the imitation basalt particles can greatly improve the strength of concrete and asphalt. Second, the granular imitation basalt material will not produce needle-like objects similar to asbestos, which reduces the harm of the imitation basalt material to the human lungs. Third, it solves the problem of environmental pollution and resource waste caused by the accumulation of red mud and gold tailings, as well as the shortage of basalt as a strategic resource. Fourth, compared with the production process of basalt fiber, this solution simplifies the steps and reduces the production cost. DETAILED DESCRIPTION

[0032] Example:

[0033] A method for preparing a new basalt-like material by using red mud and gold tailings in a coordinated manner comprises the following steps:

[0034] Step 1, raw material processing;

[0035] The gold tailings slurry discharged from the concentrator is sorted by a cyclone, and the slurry below 200 mesh is concentrated and filtered by a concentrator to obtain gold tailings with a moisture content of 15-25%; red mud with a moisture content of less than 5% is selected and crushed by a double-roll crusher;

[0036] Step 2, mixing materials;

[0037] The gold tailings and red mud in step 1 are sent to a vertical turbulent mixer for mixing and stirring, and an admixture is added during the stirring period to obtain a mixed material after the stirring is completed;

[0038] Step three, material granulation;

[0039] The mixed material in step 2 is sent to a roasting kiln for calcination, and after calcination, it is sent to a cooler to cool to below 50°C, and then the cooled mixed material is crushed by a crusher and sent to a stirring kettle, and a first impregnating agent is added to the stirring kettle. After stirring, the material in the stirring kettle is sent to a high-pressure double-roll granulator for extrusion granulation to obtain a raw material, and the raw material is filtered through a vibrating screen and sent to a drying device for drying, and primary particles are obtained after drying;

[0040] Step 4: spraying the wetting agent;

[0041] The primary particles are sent to the spraying equipment to spray the second impregnating agent. After the spraying is completed, they are left to stand for 2-3 hours, and then sent to the drying equipment for drying again to obtain the imitation basalt particles. The imitation basalt particles are waited to cool naturally to 40°C, and then packaged and stored.

[0042] In step 2, by weight, the red mud is 40-55 parts, the gold tailings is 20-40 parts, and the admixture is 5-20 parts.

[0043] The admixture is composed of gypsum, fly ash and coal gangue powder; by weight, the gypsum is 10-30 parts, the fly ash is 10-30 parts, and the coal gangue powder is 10-40 parts.

[0044] In step three, the mixed material is continuously fed into the kiln tail of the roasting kiln, the temperature range of the kiln tail is 650-750°C, the temperature range of the kiln head is 1100-1500°C, and the firing time is 30-50min.

[0045] In step three, by weight, the first impregnating agent is 25-35 parts, and the mixed material is 65-75 parts.

[0046] The first impregnating agent is composed of a first film-forming agent, a first coupling agent, polysorbate-20, silicone oil and deionized water, wherein the first film-forming agent is 10-18 parts, the first coupling agent is 7-11 parts, polysorbate-20 is 2-6 parts, silicone oil is 3-4 parts, and the rest is supplemented by deionized water. Since the imitation basalt material in this solution is granular, it does not need to be processed by wire drawing, and the material in this solution is mainly used in the field of construction, so the first impregnating agent can omit the antistatic agent to reduce costs.

[0047] In order to ensure that the imitation basalt material can enhance the various properties of the building, the impregnating agent in this scheme is divided into a first impregnating agent and a second impregnating agent, wherein the first impregnating agent is a starch-type impregnating agent, and its main function is to enhance the tensile strength, shear resistance and adhesion of the imitation basalt material. For this reason, the first impregnating agent needs to be added to the mixed material after calcination.

[0048] In the first impregnating agent, polysorbate-20 is used as an emulsifier, and silicone oil is used as a defoaming agent.

[0049] The first film-forming agent is obtained by modifying amylose with a modifier, wherein the amylose includes but is not limited to corn starch, sweet potato starch, and potato starch, and the modifier is composed of a mixture of aluminum phosphate, diaminophosphoric acid, diethanolamine, and deionized water. In terms of weight, the modifier consists of 13-15 parts of aluminum phosphate, 16-25 parts of diaminophosphoric acid, 22-30 parts of diethanolamine, and 30-49 parts of deionized water.

[0050] The first coupling agent is composed of a mixture of 40-45 parts of γ-aminopropyltriethoxysilane, 25-35 parts of γ-methacryloxypropyltrimethoxysilane, and 20-25 parts of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.

[0051] In order to enhance the acid and alkali resistance and corrosion resistance of the imitation basalt material, this solution introduces a second impregnant. The second impregnant is sprayed on the surface of the primary particles in a spraying manner, wherein the coverage rate of the second impregnant on the surface of the primary particles is not less than 97%. This design forms a protective film on the surface of the imitation basalt material to reduce the degree of corrosion of the imitation basalt particles by the external environment.

[0052] In order to ensure that the second wetting agent enhances the corrosion resistance of the square basalt particles, the second wetting agent is composed of a second film-forming agent, a second coupling agent, lauryl alcohol, hexadecyltrimethylammonium chloride and deionized water. By weight, the second film-forming agent is 12-15 parts, the second coupling agent is 5-7 parts, the lauryl alcohol is 3-5 parts, the hexadecyltrimethylammonium chloride is 1-3 parts, and the rest is supplemented by deionized water.

[0053] The second film-forming agent is waterborne polyurethane.

[0054] The second coupling agent is composed of triethanolamine borate and dibutyl boric acid ethanolamine ester mixed in a ratio of 1:1 by weight.

[0055] Embodiment 1:

[0056] The above method is used to produce the imitation basalt material, wherein:

[0057] In step 1, the moisture content of the gold tailings is 15%;

[0058] In step 2, by weight, the red mud is 40 parts, the gold tailings is 20 parts, and the admixture is 5 parts; the admixture is composed of gypsum, fly ash and coal gangue powder; by weight, the gypsum is 10 parts, the fly ash is 10 parts, and the coal gangue powder is 10 parts;

[0059] In step 3, the mixed material is continuously fed from the kiln tail of the roasting kiln, the temperature range of the kiln tail is 650°C, the temperature range of the kiln head is 1100°C, and the firing time is 50 minutes;

[0060] In step 3, the first wetting agent is 25 parts and the mixed material is 65 parts by weight;

[0061] The first impregnating agent is composed of a first film-forming agent, a first coupling agent, polysorbate-20, silicone oil and deionized water. By weight, the first film-forming agent is 10 parts, the second coupling agent is 7 parts, polysorbate-20 is 2 parts, silicone oil is 3 parts, and the rest is supplemented by deionized water.

[0062] The straight-chain starch is corn starch, and the modifier is composed of a mixture of aluminum phosphate, diaminophosphoric acid, diethanolamine and deionized water. In terms of weight, the modifier is composed of 13 parts of aluminum phosphate, 16 parts of diaminophosphoric acid, 22 parts of diethanolamine and 30 parts of deionized water.

[0063] The first coupling agent is composed of a mixture of 40 parts of γ-aminopropyltriethoxysilane, 25 parts of γ-methacryloxypropyltrimethoxysilane, and 20 parts of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.

[0064] In step 4, after spraying is completed, let it stand for 2 hours; the second wetting agent is composed of a second film-forming agent, a second coupling agent, lauryl alcohol, hexadecyltrimethylammonium chloride and deionized water. By weight, the second film-forming agent is 12 parts, the second coupling agent is 5 parts, lauryl alcohol is 3 parts, hexadecyltrimethylammonium chloride is 1 part, and the rest is supplemented by deionized water.

[0065] Embodiment 2:

[0066] The difference between this embodiment and embodiment 1 is that:

[0067] In step 1, the moisture content of the gold tailings is 17%;

[0068] In step 2, by weight, the red mud is 42 parts, the gold tailings is 25 parts, and the admixture is 10 parts; the admixture is composed of gypsum, fly ash and coal gangue powder; by weight, the gypsum is 15 parts, the fly ash is 15 parts, and the coal gangue powder is 15 parts;

[0069] In step 3, the mixed material is continuously fed from the kiln tail of the roasting kiln, the temperature range of the kiln tail is 680°C, the temperature range of the kiln head is 1200°C, and the firing time is 40 minutes;

[0070] In step 3, by weight, the first wetting agent is 27 parts and the mixed material is 67 parts;

[0071] In terms of weight, the first film-forming agent comprises 12 parts, the second coupling agent comprises 8 parts, polysorbate-20 comprises 4 parts, silicone oil comprises 3.2 parts, and the remainder is supplemented by deionized water.

[0072] The straight-chain starch is sweet potato starch, and the modifier consists of 13.5 parts of aluminum phosphate, 18 parts of diaminophosphoric acid, 24 parts of diethanolamine and 32 parts of deionized water in parts by weight.

[0073] The first coupling agent is composed of 41 parts of γ-aminopropyltriethoxysilane, 27 parts of γ-methacryloxypropyltrimethoxysilane, and 22 parts of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.

[0074] In step 4, after spraying, stand for 2.4 hours; by weight, 12.5 parts of the second film-forming agent, 5.3 parts of the second coupling agent, 3.4 parts of lauryl alcohol, 1.6 parts of hexadecyltrimethylammonium chloride, and the rest is supplemented by deionized water.

[0075] Embodiment 3:

[0076] The difference between this embodiment and embodiment 1 is that:

[0077] In step 1, the moisture content of the gold tailings is 20%;

[0078] In step 2, by weight, the red mud is 45 parts, the gold tailings is 35 parts, and the admixture is 15 parts; the admixture is composed of gypsum, fly ash and coal gangue powder; by weight, the gypsum is 22 parts, the fly ash is 22 parts, and the coal gangue powder is 25 parts;

[0079] In step 3, the mixed material is continuously fed from the kiln tail of the roasting kiln, the temperature range of the kiln tail is 710°C, the temperature range of the kiln head is 1400°C, and the firing time is 35 minutes;

[0080] In step 3, the first wetting agent is 30 parts and the mixed material is 70 parts by weight;

[0081] By weight, the first film-forming agent comprises 16 parts, the second coupling agent comprises 9 parts, polysorbate-20 comprises 5 parts, silicone oil comprises 3.7 parts, and the remainder is supplemented by deionized water.

[0082] The straight-chain starch is potato starch, and the modifier consists of 14 parts of aluminum phosphate, 20 parts of diaminophosphoric acid, 26 parts of diethanolamine and 40 parts of deionized water, calculated by weight.

[0083] The first coupling agent is composed of 43 parts of γ-aminopropyltriethoxysilane, 30 parts of γ-methacryloxypropyltrimethoxysilane, and 24 parts of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.

[0084] In step 4, after spraying, the mixture is allowed to stand for 2.6 hours; by weight, 14 parts of the second film-forming agent, 6 parts of the second coupling agent, 4 parts of lauryl alcohol, 2 parts of hexadecyltrimethylammonium chloride, and the rest is supplemented by deionized water.

[0085] Embodiment 4:

[0086] The difference between this embodiment and embodiment 1 is that:

[0087] In step 1, the moisture content of the gold tailings is 25%;

[0088] In step 2, by weight, the red mud is 55 parts, the gold tailings is 40 parts, and the admixture is 20 parts; the admixture is composed of gypsum, fly ash and coal gangue powder; by weight, the gypsum is 30 parts, the fly ash is 30 parts, and the coal gangue powder is 40 parts;

[0089] In step 3, the mixed material is continuously fed from the kiln tail of the roasting kiln, the temperature range of the kiln tail is 750°C, the temperature range of the kiln head is 1500°C, and the firing time is 50 minutes;

[0090] In step 3, by weight, the first wetting agent is 35 parts and the mixed material is 75 parts;

[0091] By weight, the first film-forming agent comprises 18 parts, the second coupling agent comprises 11 parts, polysorbate-20 comprises 6 parts, silicone oil comprises 4 parts, and the remainder is supplemented by deionized water.

[0092] The straight-chain starch is composed of a mixture of corn starch, sweet potato starch and potato starch. The modifier is composed of 15 parts of aluminum phosphate, 25 parts of diaminophosphoric acid, 30 parts of diethanolamine and 49 parts of deionized water in parts by weight.

[0093] The first coupling agent is composed of a mixture of 45 parts of γ-aminopropyltriethoxysilane, 35 parts of γ-methacryloxypropyltrimethoxysilane, and 25 parts of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.

[0094] In step 4, after spraying, the mixture is allowed to stand for 3 hours; by weight, 15 parts of the second film-forming agent, 7 parts of the second coupling agent, 5 parts of lauryl alcohol, 3 parts of hexadecyltrimethylammonium chloride, and the rest is supplemented by deionized water.

[0095] Comparative Example 1:

[0096] The difference between this comparative example and Example 1 is that the first wetting agent is not used in this comparative example.

[0097] Comparative Example 2:

[0098] The difference between this comparative example and Example 1 is that in this comparative example, the amount of the first impregnating agent is 10 parts, and the amount of the mixed material is 90 parts.

[0099] Comparative Example 3:

[0100] The difference between this comparative example and Example 1 is that in this comparative example, the amount of the first impregnating agent is 15 parts, and the amount of the mixed material is 85 parts.

[0101] Comparative Example 4:

[0102] The difference between this comparative example and Example 1 is that in this comparative example, the second impregnating agent is not used.

[0103] Comparative Example 5:

[0104] In this comparative example, the coverage rate of the second wetting agent on the primary particles is 90%. As a variable, the coverage rates of other embodiments and comparative examples are not less than 97%.

[0105] Comparative Example 6:

[0106] The difference between this comparative example and Example 1 is that the first coupling agent is not used in the first impregnating agent.

[0107] Comparative Example 7:

[0108] The difference between this comparative example and Example 1 is that the amylose in the first impregnating agent is not modified by a modifying agent.

[0109] Comparative Example 8:

[0110] The difference between this comparative example and Example 1 is that no second coupling agent is used in the second impregnating agent.

[0111] Take the final products in Example 1 to Example 4 and Comparative Example 1 to Comparative Example 8, and test the slump, compressive strength, and chloride ion penetration and diffusion of the concrete by measuring the fluidity of the concrete through the slump according to the "Concrete Quality Control Standard" (GB50164-92).

[0112] Among them, during the compressive strength test, the final product was mixed with concrete at a ratio of 1:8 by weight, and other additives were used normally. The test used a rectangular block with a bottom side length of 100mm×50mm and a height of 120mm. The test was carried out when the standard curing lasted for 25 days. The results are shown in the following table:

[0113]

[0114] It can be seen from the data of Comparative Example 1, Comparative Example 2 and Example 1 that whether the first impregnating agent is used and the amount used will affect the final experimental data of the concrete block. Even if the amount of the first impregnating agent is small, it greatly optimizes the compressive strength and electric flux of the concrete block.

[0115] It can be seen from Comparative Examples 4 and 5 that whether the second impregnating agent is used and the amount of the second impregnating agent used also greatly affect the quality of the final product.

[0116] The final products in Examples 1 to 4 and Comparative Examples 1 to 8 were taken, and the final products were mixed with asphalt at a mass ratio of 1:50, and the performance indicators of the asphalt after paving were tested. The results are as follows:

[0117]

[0118] It can be seen from the above table that this product also greatly improves the strength of asphalt.

[0119] In summary, this solution has the following advantages: First, through the combined use of the first impregnating agent and the second impregnating agent, the imitation basalt particles can greatly improve the strength of concrete and asphalt. Second, the granular imitation basalt material will not produce asbestos-like needles, which reduces the harm of the imitation basalt material to the human lungs. Third, it solves the problem of environmental pollution and waste of resources caused by the accumulation of red mud and gold tailings, as well as the shortage of basalt as a strategic resource. Fourth, compared with the production process of basalt fiber, this solution simplifies the steps and reduces the production cost.

[0120] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.

Claims

1. A method for preparing basalt-like material by synergistically using red mud and gold tailings, characterized in that: The steps include: Step 1, raw material processing; The gold tailings slurry discharged from the concentrator is sorted by a cyclone, and the slurry below 200 mesh is concentrated and filtered by a concentrator to obtain gold tailings with a moisture content of 15-25%; red mud with a moisture content of less than 5% is selected and crushed by a double-roll crusher; Step 2, mixing materials; The gold tailings and red mud in step 1 are sent to a vertical turbulent mixer for mixing and stirring, and an admixture is added during the stirring period to obtain a mixed material after the stirring is completed; Step three, material granulation; The mixed material in step 2 is sent to a roasting kiln for calcination, and after calcination, it is sent to a cooler to cool to below 50°C, and then the cooled mixed material is crushed by a crusher and sent to a stirring kettle, and a first impregnating agent is added to the stirring kettle. After stirring, the material in the stirring kettle is sent to a high-pressure double-roll granulator for extrusion granulation to obtain a raw material, and the raw material is screened by a vibrating screen and sent to a drying device for drying, and primary particles are obtained after drying; Step 4: spraying the wetting agent; The primary particles are sent to the spraying equipment to spray the second impregnating agent, and after the spraying is completed, they are left to stand for 2-3 hours, and then sent to the drying equipment for drying again to obtain the imitation basalt particles, and the imitation basalt particles are waited to cool naturally to 40°C, and then packaged and stored; In step 3, the first wetting agent is 25-35 parts by weight, and the mixed material is 65-75 parts by weight; The first impregnating agent is composed of a first film-forming agent, a first coupling agent, polysorbate-20, silicone oil and deionized water, wherein, by weight, the first film-forming agent is 10-18 parts, the first coupling agent is 7-11 parts, polysorbate-20 is 2-6 parts, silicone oil is 3-4 parts, and the rest is supplemented by deionized water; The first film-forming agent is obtained by modifying amylose with a modifier, wherein the amylose includes but is not limited to corn starch, sweet potato starch, and potato starch, and the modifier is composed of a mixture of aluminum phosphate, diaminophosphoric acid, diethanolamine, and deionized water, and the modifier is composed of 13-15 parts of aluminum phosphate, 16-25 parts of diaminophosphoric acid, 22-30 parts of diethanolamine, and 30-49 parts of deionized water in parts by weight; The first coupling agent is composed of 40-45 parts of γ-aminopropyltriethoxysilane, 25-35 parts of γ-methacryloxypropyltrimethoxysilane, and 20-25 parts of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane; The second wetting agent is composed of a second film-forming agent, a second coupling agent, lauryl alcohol, hexadecyl trimethyl ammonium chloride and deionized water, wherein, by weight, the second film-forming agent is 12-15 parts, the second coupling agent is 5-7 parts, the lauryl alcohol is 3-5 parts, the hexadecyl trimethyl ammonium chloride is 1-3 parts, and the rest is supplemented by deionized water; The second film-forming agent is waterborne polyurethane; and the second coupling agent is a boric acid ester coupling agent.

2. The method for preparing basalt-like material by synergistically using red mud and gold tailings according to claim 1, characterized in that: In step 2, by weight, the red mud is 40-55 parts, the gold tailings is 20-40 parts, and the admixture is 5-20 parts.

3. The method for preparing basalt-like material by synergistically using red mud and gold tailings according to claim 2, characterized in that: The admixture is composed of gypsum, fly ash and coal gangue powder; by weight, the gypsum is 10-30 parts, the fly ash is 10-30 parts, and the coal gangue powder is 10-40 parts.

4. The method for preparing basalt-like material by synergistically using red mud and gold tailings according to claim 1, characterized in that: In step three, the mixed material is continuously fed into the kiln tail of the roasting kiln, the temperature range of the kiln tail is 650-750°C, the temperature range of the kiln head is 1100-1500°C, and the firing time is 30-50min.

Citation Information

Patent Citations

  • A method for preparing continuous basalt fiber with industrial solid waste as raw material

    CN104261669B

  • Method for preparing continuous basalt fiber with industry waste solid as raw material

    CN104261669A

  • Imitated basalt fiber

    CN109650730A